Epstein-Barr viral miRNAs inhibit antiviral CD4(+) T cell responses targeting IL-12 and peptide processing - Tagawa, Takanobu (J Exp Med, 2016)
Epstein-Barr virus (EBV) is a tumor virus that establishes lifelong infection in most of humanity, despite eliciting strong and stable virus-specific immune responses. EBV encodes at least 44 miRNAs, most of them with unknown function. Here, we show that multiple EBV miRNAs modulate immune recognition of recently infected primary B cells, EBV's natural target cells. EBV miRNAs collectively and specifically suppress release of proinflammatory cytokines such as IL-12, repress differentiation of naive CD4(+) T cells to Th1 cells, interfere with peptide processing and presentation on HLA class II, and thus reduce activation of cytotoxic EBV-specific CD4(+) effector T cells and killing of infected B cells. Our findings identify a previously unknown viral strategy of immune evasion. By rapidly expressing multiple miRNAs, which are themselves nonimmunogenic, EBV counteracts recognition by CD4(+) T cells and establishes a program of reduced immunogenicity in recently infected B cells, allowing the virus to express viral proteins required for establishment of life-long infection.